Ferroelectric hysteresis loops as the manifestation of interface-aided polarization reversals in heterostructures - Chew, Khian Hooi; Shin, F.G.; Ishibashi, Y. (2005)
We present a detailed study of intrinsic ferroelectric hysteresis loops in a hetreostructure of interface between two different ferroelectrics of the second-order transition by the Landu-Ginzburg theory. Our study indicates that the ferroelectric hysteresis behavior in an interfacial-coupled structure might be governed by the interplay of various parameters such as the interfacial coupling, the interaction between neighboring polarizations within the constituents and the dielectric softness of the constituents. Inhomogeneity of polarization at the interface induced by the interaction between the constituents across the interface assists the polarization reversal by reducing the coercive field of the hetreostructures, implying an interface-aided polarization reversal. a significant reduction in the coercieve field of the interface structure is expected to be possible if the certain conditions based on the above-mentioned parameters are achieved.